The gene signature of tertiary lymphoid structures within ovarian cancer predicts the prognosis and immunotherapy benefit - Hou, Yue; Qiao, Sijing; Li, Miao; Han, Xue; Wei, Xuan; Pang, Yingxin; Mao, Hongluan (Frontiers in Genetics, 2023)
Ovarian cancer (OC) has the lowest survival rate among gynecologic malignancies. Ectopic lymphocyte aggregates, namely tertiary lymphoid structures (TLSs), have been reported as positive biomarkers for tumor prognosis. However, the related gene signature of TLS in ovarian cancer was less understood. Therefore, this study first exhibited the organizational patterns of TLS by H&E staining and immunohistochemistry (IHC) and confirmed the improved survival values of TLS and quantified tumor-infiltrating lymphocytes (CD20 B cells and CD8T cells) in ovarian cancer patients. Secondly, we collected the genes involved in TLS from databases. By the univariate regression analysis, the TLS gene signature (CETP, CCR7, SELL, LAMP3, CCL19, CXCL9, CXCL10, CXCL11, CXCL13) with prognostic value, characteristically of ovarian cancer, was constructed in the TCGA dataset and validated in the GSE140082 dataset. Thirdly, by performing CIBERSORT and Tumor Immune Dysfunction and Exclusion (TIDE) analysis, we found that the high expression of this gene signature was positively correlated with developed immune infiltration and reduced immune escape. The improved IPS score and application in the IMvigor210 dataset received PD-L1 proved the predictive value of immunotherapy for this gene signature. Furthermore, this signature showed a better correlation between tumor mutation burden and classical checkpoint genes. In conclusion, TLS plays important role in tumor immunity and the gene signature can be evaluated as a biomarker for predicting prognosis and guiding immunotherapy in OC.